Estimation of Shelf Life Pasta Spice for Dekke Mas Na Niura with the Accelerated Shelf Life Test (ASLT) Method Arrhenius Equation - Natalia Putri Erva Simbolon; Bhakti Etza Setiani; Anang Mohammad Legowo (Journal of Applied Food Technology, 2019)
Dekke mas na niura is a typical local food of North Sumatra made from carp which does not undergo cooking processes such as frying, steaming, burning, or boiling but is only paraded. This study aimed to estimate the shelf life of pasta spices using the Arrhenius equation model Accelerated Shelf Life Test (ASLT). This research was conducted at the Laboratory of Food Chemistry and Nutrition, Faculty of Animal Husbandry and Agriculture, Diponegoro University, Semarang. The materials used in making spices dekke mas na niura were andaliman, pecan, turmeric, kecombrang / rias, onion, garlic, salt, red chili, lime, kaffir lime, galangal, and peanuts. The method used for making pasta spices is by mixing spices and grinding ingredients until smooth. Spices are stored at 25°C, 30°C, 35°C and 40°C for 24 hours of storage. The Analysis is carried out every 6 hours. The parameters tested were Aw value, pH value, and total bacteria (TPC). The results of the test data were then made linear regression with the making of ordes 0 and orde 1, then from the data, the shelf life calculation was done with the Arrhenius equation. The results showed that the highest Aw, pH, and total bacterial values were at 40°C which were stored for 24 hours. The critical point used in estimating shelf life was total bacterial orde 1. Estimation of shelf life based on total bacteria was 5.6 days (25°C); 7.1 days (30°C); 5.6 days (35°C); and 5.2 days (40°C). Storage of pasta ingredients dekke mas na niura optimum at 30°C. Overall, the higher the storage temperature and storage time, the shorter the shelf life.